PENJADWALAN FLOW SHOP DENGAN PENDEKATAN CROSS ENTROPY-GENETIC ALGORITHM UNTUK MENURUNKAN MAKESPAN PADA PEMBUATAN RODA GIGI - Widodo, Dian Setiya; Ellianto, Mario Sarisky Dwi (Heuristic, 2015)
Flow shop is the process of determining the sequence of jobs that have the same product path. While the flow-shop scheduling takes assumption that a number of jobs that each has the same machine work sequence. The problems faced by com-panies, namely the high demand and yet the existence of a good scheduling planning resulted in the company should be able to optimize sche-duling job. One of the ways to solve these problems is by minimizing the Makespan. This research will solve the problem regarding to the flow shop scheduling by using cross entropy-genetic algorithm (CEGA) method to minimize Makespan. The technique that is used to solve the problem is by comparing the result of the application of existing methods in the company with the proposed method (CEGA). To support the application of CEGA used MATLAB software. Finally known that the results CEGA can give optimal solution, Makespan values obtained for 10829 seconds. So far, it was more effective than the method that used at the firm with Makespan efficiency by 10.06%.Keywords: Flow Shop, Scheduling, Cross Entropy-Genetic Algorithm, Makespan.